Glycosaminoglycans and Proteoglycans - Vitor H. Pomin; Barbara Mulloy (MDPI AG, 2018)
In this editorial to MDPI Pharmaceuticals special issue "Glycosaminoglycans and Proteoglycans" we describe in outline the common structural features of glycosaminoglycans and the characteristics of proteoglycans, including the intracellular proteoglycan, serglycin, cell-surface proteoglycans, like syndecans and glypicans, and the extracellular matrix proteoglycans, like aggrecan, perlecan, and small leucine-rich proteoglycans. The context in which the pharmaceutical uses of glycosaminoglycans and proteoglycans are presented in this special issue is given at the very end.